Implementation of Work Quality in Improving Performance - Utama, Handoko; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
Humankind holds a very important position in any organization because humans play an important role in daily life activities, especially in the workplace environment. Humans are seen by God as the purest form of life because they have a personality that is different from other forms of life. Without human resources, a business cannot carry out its activities, so human resources are very important. The results of this research are as follows: Organizational climate has a positive and insignificant effect with an original sample value of 0.026 and ap value of 0.421. Organizational climate has a positive and significant effect on work quality with an original sample of 0.777 and ap value of 0.000. Work Quality has a positive and significant effect on Employee Performance with an original sample of 0.595 and ap value of 0.000. The work environment has a positive and significant effect on employee performance with an original sample value of 0.354 and ap value of 0.020. Work Environment has a positive and insignificant effect on Work Quality with an original sample value of 0.146 and ap value of 0.242. Organizational climate has a positive and significant effect on employee performance through work quality indirectly with an original sample value of 0.462 and ap value of 0.004. Work Environment has a positive and insignificant effect on Employee Performance through Work Quality indirectly with an original sample value of 0.087 and ap value of 0.242.